EQUIVALENCE IN TRANSLATION - Axmedova Muhayyo; Tirkasheva Shahnoza (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstarct: Every translation can be regarded as belonging to a certain type of equivalence. Since each subsequent type implies a higher degree of semantic similarity we can say that every translation is made at a certain level of equivalence.